Non-structural Carbohydrates in Dormant Woody Perennials; The Tale of Winter Survival and Spring Arrival - Tixier, Aude; Gambetta, Gregory A.; Godfrey, Jessie; Orozco, Jessica; Zwieniecki, Maciej A. (Frontiers in Forests and Global Change, 2019)
Woody perennials’ reliance on nonstructural carbohydrates (NSC) reserves for the resumption of spring growth necessitates an accumulation of NSC prior to dormancy. It is assumed that during dormancy temperature-regulated biological activities gauge the progression of winter and affect the metabolic rates and physiology of NSC reserves. Thus, changes in temperature signal the arrival of spring and determine the amount of reserves available for growth resumption. As woody perennials are dependent on dispersed storage of NSC during spring, they need an integrated remobilization and redistribution for synchronous and effective development of photosynthetic and reproductive organs. However, it is not known how storage compartments interact at the whole plant level, when NSC reserves are mobilized, or how local and distal storage compartments influence the biology of spring growth resumption. The goal of this mini-review is to shift the focus of winter biology from bud-centric to the whole plant. We discuss winter NSC management in the context of climate change with a special emphasis on how projected mild winters may affect the carbon budget, transport, and allocation during winter. We look at three aspects of NSC regulation underlying dormancy (I) the molecular regulation of dormancy (II) temperature dependent winter NSC metabolism, and (III) spring NSC remobilization and redistribution processes.